KEBIJAKAN RETROAKTIF DALAM PENEGAKAN HUKUM TERHADAP PELANGGARAN HAK ASASI MANUSIA YANG BERAT - Ahmad Basuki (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
The article entitling “The Retroactive Policy in the straightening of law to the gross violation of Human Right in Indonesia